Impact of Wall Impedance Phase Angle on Indoor Sound Field and Reverberation Parameters Derived from Room Impulse Response - MEISSNER, Mirosław; ZIELINSKI, Tomasz (Archives of Acoustics, 2022)
Accurate definition of boundary conditions is of crucial importance for room acoustic predictions because the wall impedance phase angle can affect the sound field in rooms and acoustic parameters applied to assess a room reverberation. In this paper, the issue was investigated theoretically using the convolution integral and a modal representation of the room impulse response for complex-valued boundary conditions. Theoretical considerations have been accompanied with numerical simulations carried out for a rectangular room. The case of zero phase angle, which is often assumed in room acoustic simulations, was taken as a reference, and differences in the sound pressure level and decay times were determined in relation to this case. Calculation results have shown that a slight deviation of the phase angle with respect to the phase equal to zero can cause a perceptual difference in the sound pressure level. This effect was found to be due to a change in modal frequencies as a result of an increase or decrease in the phase angle. Simulations have demonstrated that surface distributions of decay times are highly irregular, while a much greater range of the early decay time compared to the reverberation time range indicates that a decay curve is nonlinear. It was also found that a difference between the decay times predicted for the complex impedance and real impedance is especially clearly audible for the largest impedance phase angles because it corresponds approximately to 4 just noticeable differences for the reverberation metrics.